A head and neck cancer intervention for use in survivorship clinics: a protocol for a feasibility study. Issue 1 (December 2016) - Salz, Talya; McCabe, Mary S.; Oeffinger, Kevin C.; Corcoran, Stacie; Vickers, Andrew J.; Salner, Andrew L.; Dornelas, Ellen; Schnall, Rebecca; Raghunathan, Nirupa J.; Fortier, Elizabeth; Baxi, Shrujal S.
Abstract Background Head and neck cancer survivors commonly experience severe long-term toxicities, late-occurring symptoms, and significant risks of the second primary malignancy and comorbid illnesses. With multiple simultaneous health issues, these complex cancer survivors often do not receive comprehensive health care that addresses their needs. A tool is needed to streamline and standardize comprehensive care for this cohort. Methods/design We designed the Head and Neck Survivorship Tool: Assessment and Recommendations (HN-STAR) to address health care challenges for head and neck cancer survivors. HN-STAR is an electronic platform that aims to simplify the provision of personalized care in cancer survivorship clinics. It uses an algorithmic approach to integrate patient-reported outcomes, clinical details, and evidence-based guidelines to standardize comprehensive care provided in routine survivorship visits. It has four integrated components: (1) a simplifiedtreatment summary, which pulls treatment details from a clinical database or can be completed manually using a streamlined form; (2) an onlineself-assessment for patients to report their own symptoms; (3) an interactivediscussion guide presenting all relevant information to the provider during the clinic visit; and (4) asurvivorship care plan generated at the end of each visit that reflects decisions made during the visit. By using a modifiable electronic platform, HN-STAR provides a method for incorporating survivorship care plans into clinical practice and for disseminating evidence on symptom management and preventive care. This is a study to assess the feasibility of a future multi-site, randomized clinical trial of HN-STAR. We will enroll head and neck cancer survivors who are followed in one of two nurse practitioner-led survivorship clinics. We will implement HN-STAR for one routine survivorship visits. We will assess (1) usability and feasibility outcomes of HN-STAR from the perspective of key stakeholders and (2) the planned outcomes intended for the larger trial. We will collect usability and feasibility data from online surveys of survivors and their providers. Our findings will inform whether it is feasible to advance HN-STAR to trial. If so, we will adapt HN-STAR and the study design of the trial in response to feedback from survivors and providers. The long-term goal is to determine if such an intervention will lead to improved and simplified comprehensive survivorship care. Discussion This feasibility study will evaluate implementation of HN-STAR into clinical practice in terms of usability, practicality, and clinical flow in two distinct clinical settings. This study will also provide critical baseline data to characterize this vulnerable population. Findings from this study will inform a multicenter randomized trial of HN-STAR, aimed at standardizing and streamlining the delivery of evidence-guided comprehensive care for head and neck cancer survivors. Ultimately, if found effective, the modular structure of HN-STAR could permit its expansion to survivors of other complex cancers. Trial registration ClinicalTrials.gov, NCT02571673